2019
DOI: 10.1158/0008-5472.can-18-1492
|View full text |Cite
|
Sign up to set email alerts
|

Differential Subcellular Localization Regulates Oncogenic Signaling by ROS1 Kinase Fusion Proteins

Abstract: Chromosomal rearrangements involving receptor tyrosine kinases (RTK) are a clinically relevant oncogenic mechanism in human cancers. These chimeric oncoproteins often contain the C-terminal kinase domain of the RTK joined in cis to various N-terminal, nonkinase fusion partners. The functional role of the N-terminal fusion partner in RTK fusion oncoproteins is poorly understood. Here, we show that distinct N-terminal fusion partners drive differential subcellular localization, which imparts distinct cell signal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 49 publications
1
48
0
2
Order By: Relevance
“…The data are consistent with SHP2/MEK/ERK activation being the principal effector of FGFR in normal physiology (38) and with the frequent presence of concurrent PIK3CA activating mutations with FGFR2 fusions in ICC, indicating the potential independence of these pathways (14). Although our studies suggested that FGFR2 fusions with different partners had comparable outputs, further studies will be required to fully address the potential differential impact of N-terminus partners on oncoprotein localization, inhibitor sensitivity, and downstream signaling targets, as reported for fusions involving the ROS1 receptor tyrosine kinase (39).…”
Section: Discussionmentioning
confidence: 62%
“…The data are consistent with SHP2/MEK/ERK activation being the principal effector of FGFR in normal physiology (38) and with the frequent presence of concurrent PIK3CA activating mutations with FGFR2 fusions in ICC, indicating the potential independence of these pathways (14). Although our studies suggested that FGFR2 fusions with different partners had comparable outputs, further studies will be required to fully address the potential differential impact of N-terminus partners on oncoprotein localization, inhibitor sensitivity, and downstream signaling targets, as reported for fusions involving the ROS1 receptor tyrosine kinase (39).…”
Section: Discussionmentioning
confidence: 62%
“…Neel et al. [50] recently reported that clinically relevant ROS1 RTK fusion oncoproteins show differential subcellular localizations, which impart distinct cell signaling and oncogenic properties. When ROS1 fusion proteins are localized to endosomes, the strongest activations of MAPK signaling are observed.…”
Section: Subcellular Localization Of Receptor Tyrosine Kinases May Gementioning
confidence: 99%
“…Similarly, the endosome-localized fusion proteins SDC4-ROS1 and SLC34A2-ROS1 and endoplasmic reticulum-localized fusion protein CD74-ROS1 differentially activate mitogen-activated protein kinase (MAPK) (Neel et al, 2019). A study has shown that ROS1 localizes to the cytoplasm in majority of OSCCs, whereas it localizes predominantly to the nucleus in adjacent dysplastic epithelial tissues (Cheng et al, 2015).…”
Section: Introductionmentioning
confidence: 99%